Chemical Hypoxia Brings to Light Altered Autocrine Sphingosine-1-Phosphate Signalling in Rheumatoid Arthritis Synovial Fibroblasts - Chenqi Zhao; Uriel Moreno-Nieves; John A. Di Battista; Maria J. Fernandes; Mohamed Touaibia; Sylvain G. Bourgoin (Hindawi Limited, 2015)
Emerging evidence suggests a role for sphingosine-1-phosphate (S1P) in various aspects of rheumatoid arthritis (RA) pathogenesis. In this study we compared the effect of chemical hypoxia induced by cobalt chloride (CoCl2) on the expression of S1P metabolic enzymes and cytokine/chemokine secretion in normal fibroblast-like synoviocytes (FLS) and RAFLS. RAFLS incubated with CoCl2, but not S1P, produced less IL-8 and MCP-1 than normal FLS. Furthermore, incubation with the S1P2 and S1P3 receptor antagonists, JTE-013 and CAY10444, reduced CoCl2-mediated chemokine production in normal FLS but not in RAFLS. RAFLS showed lower levels of intracellular S1P and enhanced mRNA expression of S1P phosphatase 1 (SGPP1) and S1P lyase (SPL), the enzymes that are involved in intracellular S1P degradation, when compared to normal FLS. Incubation with CoCl2 decreased SGPP1 mRNA and protein and SPL mRNA as well. Inhibition of SPL enhanced CoCl2-mediated cytokine/chemokine release and restored autocrine activation of S1P2 and S1P3 receptors in RAFLS. The results suggest that the sphingolipid pathway regulating the intracellular levels of S1P is dysregulated in RAFLS and has a significant impact on cell autocrine activation by S1P. Altered sphingolipid metabolism in FLS from patients with advanced RA raises the issue of synovial cell burnout due to chronic inflammation.